Design and control of a MRI-compatible pneumatic needle puncture robot. (7th October 2019) - Zhao, Baoliang; Fu, Yi; Yang, Yuanyuan; Zhang, Peng; Hu, Ying
Abstract: Percutaneous needle puncture operation is widely used in the image-guided interventions, including biopsy and ablation. MRI guidance has the advantages of high-resolution soft tissue imaging and thermal monitoring during energy-based ablation. This paper proposes the design of a 5-DOF pneumatic needle puncture robot, with all the cylinders, sensors and structure material MRI-compatible. Also, a hybrid fuzzy-PID controller is designed for the pneumatic driven system to adjust the PID parameters adaptively. The experiment validation result shows that, compared with the traditional fix-parameter PID control, the proposed hybrid fuzzy-PID control has no overshoot, and the settle time/steady state error remains low even with increasing load. This proves that the hybrid fuzzy-PID control strategy can increases the positioning accuracy and robustness of the pneumatic driven needle puncture robot, which is significant for the safety of percutaneous needle puncture operation.